An Accounting Perspective of Tax Amnesty in Indonesia - Euodia Shienny Natania; Arthik Davianti (Journal of Accounting Auditing and Business, 2018)
In 2016, the Indonesian government has issued a new tax program, which is tax amnesty. The application of tax amnesty was driven by of the global economic downturn, due to the decreasing trading activity, followed by the increasing prices of the export-import activity. In addition, the tax ratio in Indonesia is considered to be too low compared to other neighboring countries. However, as anticipated, the implementation of tax amnesty requires global information disclosures, particularly repatriation fund from overseas investments. For example, in addition to banks in Indonesia, Singapore is one of a place to invest. According to The Jakarta Post (2016), more than a half of Singapore’s economy is supported by Indonesian business people with an estimation of US$200 billion in private banking assets and 40 percent of the island’s total private banking assets. Such investments are to be disclosed in tax amnesty program. This particular disclosure as in Automatic Exchange of Information (AEoI) will start in 2018 and also the revision of banking regulation to disclose data for taxation. AEoI is already agreed in Group of Twenty’s (G-20) meeting last February in China (Merah Putih Bisnis, 2016). After arrived in this situation, taxpayers cannot conceal their asset anymore from the tax authority. The disclosures will include financial proxy war such as assets protection scheme and international planning that will inflict country financial loss (Aliandu, 2016). The Indonesian government also considered tax amnesty as a way out to solve its economic problems. Therefore, the underlying perception for that consideration is that tax amnesty is expected to gain more funds from tax based on disclosing the repatriation fund from overseas investments.